Care Bundles for Chronic Kidney Disease (CKD) Patients with Hypervolemia: Case Reports - Aqilah, Faiha Nurul; Praptiwi, Atlastieka; Yulianita, Henny (JURNAL CITRA KEPERAWATAN, 2025)
The rising prevalence of Chronic Kidney Disease (CKD) highlights its significance as a global health concern requiring comprehensive management. CKD is characterized by a progressive, irreversible decline in renal function, leading to fluid and electrolyte imbalances. One such complication is hypevolemia, which can result in serious health consequences. Our case reports evaluates the effectiveness of implementing care bundles that incorporated both independent and collaborative nursing intervention. Data collection was conducted through observation, interviews, physical examinations, and supporting data. The subjects were two stage V CKD patients with hypervolemia at Umar Wirahadikusumah Hospital in Sumedang, West Java. Over a five-day period, interventions included patient education, fluid restriction, proper positioning, breathing relaxation techniques, and collaborative treatments such as administration of diuretics, antihypertensives, hemodialysis, and ascitic fluid paracentesis.The implementation of care bundles resulted in improved clinical outcomes, including stabilized blood pressure (120–130/70–80 mmHg), decreasing abdominal circumference (6–15%), reducing dyspnea (respiratory rate 20–25 breaths/min), and increasing oxygen saturation (98–99%). Nurses play a key role as caregivers and coordinators in delivering both independent and collaborative interventions. Through an interdiciplinary approach, the implementation of care bundles has proven effective in achieving optimal care goals and improving patient health outcomes.